The VOID shell: A toolkit for the development of distributed video games and virtual worlds. - CAHILL, VINNY; TANGNEY, BRENDAN (My University, 1995)
This paper presents a brief overview of the void ap- proach to the design and implementation of next- generation (distributed) video games and other inter- active virtual world applications. The main features of the void Shell, a toolkit for object-oriented game and virtual world development, are described including its object model and associated class libraries as well as the tools provided for the game designer and program- mer.
Workshop on Simulation and Interaction in Virtual Environments
PUBLISHED
University of Iowa
Keywords: Computer Science